K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 9 2018

\(y\left(y+3\right)^2-\left(y+2\right)\left(y^2-2y+4\right)-6\left(y+5\right)\left(y-5\right)=97\)

\(y\left(y^2+6y+9\right)-\left(y^3+8\right)-6\left(y^2-25\right)=97\)

\(y^3+6y^2+9y-y^3-8-6y^2+150=97\)

\(9y=97+8-150\)

\(9y=-45\Rightarrow y=-5\)

a: \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3-1-3\left(4x^2-4x+1\right)=15\)

=>\(12x^2+6x-12x^2+12x-3=15\)

=>18x=18

=>x=1

b: \(\Leftrightarrow y^3+6y^2+9y-y^3-8-6y^2+150=97\)

=>9y+142=97

=>9y=-45

=>y=-5

13 tháng 2 2018

c.

\(4y^2+1=4y\)

\(\Leftrightarrow4y^2-4y+1=0\)

\(\Leftrightarrow4y^2-2y-2y+1=0\)

\(\Leftrightarrow2y\left(2y-1\right)-\left(2y-1\right)=0\)

\(\Leftrightarrow\left(2y-1\right)^2=0\)

\(\Leftrightarrow y=0\)

d.

\(y^2-2y=80\)

\(\Leftrightarrow y^2-2y-80=0\)

\(\Leftrightarrow y^2-10y+8y-80=0\)

\(\Leftrightarrow y\left(y-10\right)+8\left(y-10\right)=0\)

\(\Leftrightarrow\left(y+8\right)\left(y-10\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}y+8=0\\y-10=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}y=-8\\y=10\end{matrix}\right.\)

13 tháng 2 2018

thanks

2 tháng 11 2017

a) \(\left(x+3\right)\left(x+4\right)\left(x+5\right)\left(x+6\right)+1\)

\(=\left(x^2+9x+18\right)\left(x^2+9x+20\right)+1\)

\(=\left(x^2+9x+19\right)^2-1+1\)

\(=\left(x^2+9x+19\right)^2\)

b) \(x^2+y^2+2x+2y+2\left(x+1\right)\left(y+1\right)+2\)

\(=\left(x^2+2x+1\right)+\left(y^2+2y+1\right)+2\left(x+1\right)\left(y+1\right)\)

\(=\left(x+1\right)^2+\left(y+1\right)^2+2\left(x+1\right)\left(y+1\right)\)

\(=\left(x+1+y+1\right)^2=\left(x+y+2\right)^2\)

c) \(x^2-2x\left(y+2\right)+y^2+4y+4\)

\(=x^2-2x\left(y+2\right)+\left(y^2+4y+4\right)\)

\(=x^2-2x\left(y+2\right)+\left(y+2\right)^2\)

\(\left(x-y-2\right)^2\)

d) \(x^2+2x\left(y+1\right)+y^2+2y+1\)

\(=x^2+2x\left(y+1\right)+\left(y^2+2y+1\right)\)

\(=x^2+2x\left(y+1\right)+\left(y+1\right)^2\)

\(=\left(x+y+1\right)^2\)

22 tháng 7 2017

1. \(125x^3+y^6=\left(5x\right)^3+\left(y^2\right)^3\)

\(=\left(5x+y^2\right)\left[\left(5x\right)^2-5x.y^2+\left(y^2\right)^2\right]\)

\(=\left(5x+y^2\right)\left(25x^2-5xy^2+y^4\right)\)

2. \(4x\left(x-2y\right)+8y\left(2y-x\right)\)

\(=4x\left(x-2y\right)-8y\left(x-2y\right)\)

\(=\left(x-2y\right)\left(4x-8y\right)\)

3. \(25\left(x-y\right)^2-16\left(x+y\right)^2\)

\(=\left[5\left(x-y\right)\right]^2-\left[4\left(x+y\right)\right]^2\)

\(=\left[5\left(x-y\right)-4\left(x+y\right)\right]\left[5\left(x-y\right)+4\left(x+y\right)\right]\)

\(=\left(5x-5y-4x-4y\right)\left(5x-5y+4x+4y\right)\)

\(=\left(x-9y\right)\left(9x-y\right)\)

4. \(x^4-x^3-x^2+1\)

\(=x^3\left(x-1\right)-\left(x^2-1\right)\)

\(=x^3\left(x-1\right)-\left(x-1\right)\left(x+1\right)\)

\(=\left(x-1\right)\left(x^3-x-1\right)\)

5. \(a^3x-ab+b-x\)

\(=a^3x-x-ab+b\)

\(=x\left(a^3-1\right)-b\left(a-1\right)\)

\(=x\left(a-1\right)\left(a^2+a+1\right)-b\left(a-1\right)\)

\(=\left(a-1\right)\left[x\left(a^2+a+1\right)-b\right]\)

6. \(x^3-64=x^3-4^3\)

\(=\left(x-4\right)\left(x^2+4x+16\right)\)

7. \(0,125\left(a+1\right)^3-1\)

\(=\left[0,5\left(a+1\right)\right]^3-1^3\)

\(=\left[0,5\left(a+1\right)-1\right]\left\{\left[0,5\left(a+1\right)\right]^2+\left[0,5\left(a+1\right).1\right]+1^2\right\}\)

\(=\left[0,5\left(a+1-2\right)\right]\left[0,25a^2+0,5a+0,25+0,5a+0,5+1\right]\)

\(=\left[0,5\left(a-1\right)\right]\left(0,25a^2+a+1,75\right)\)

8. \(9\left(x+5\right)^2-\left(x-7\right)^2\)

\(=\left[3\left(x+5\right)\right]^2-\left(x-7\right)^2\)

\(=\left(3x+15-x+7\right)\left(3x+15+x-7\right)\)

\(=\left(2x+22\right)\left(4x+8\right)\)

9. \(49\left(y-4\right)^2-9\left(y+2\right)^2\)

\(=\left[7\left(y-4\right)\right]^2-\left[3\left(y+2\right)\right]^2\)

\(=\left(7y-28-3y-6\right)\left(7y-28+3y+6\right)\)

\(=\left(4y-34\right)\left(10y-22\right)\)

10. \(x^2y+xy^2-x-y=xy\left(x+y\right)-\left(x+y\right)\)

\(=\left(x+y\right)\left(xy-1\right)\)

11. \(x^3+3x^2+3x+1-27z^3\)

\(=\left(x+1\right)^3-\left(3z\right)^3\)

\(=\left(x+1-3z\right)\left(x^2+2x+1+3xz+3z+9z^2\right)\)

12. \(x^2-y^2-x+y=\left(x-y\right)\left(x+y\right)-\left(x-y\right)\)

\(=\left(x-y\right)\left(x+y-1\right)\)

3 tháng 9 2016

1a/ z2 - 6z + 5 - t2 - 4t = z2 - 2 . 3z + 32 - 4 - t2 - 4t = (z2 - 2 . 3z + 32) - (22 + 2 . 2t + t2) = (z - 3)2 - (2 + t)2

b/ x2 - 2xy + 2y2 + 2y2 + 1 = x2 - 2xy + y2 + y2 + 2y + 1 = (x2 - 2xy + y2) + (y2 + 2y + 1) = (x - y)2 + (y + 1)2

c/ 4x2 - 12x - y2 + 2y + 8 = (2x)2 - 12x - y2 + 2y + 32 - 1 = [ (2x)2 - 2 . 3 . 2x + 32 ] - (y2 - 2y + 1) = (2x - 3)2 - (y - 1)2

3 tháng 9 2016

2a/ (x + y + 4)(x + y - 4) = x2 + xy - 4x + xy + y2 - 4y + 4x + 4y + 16 = x2 + (xy + xy) + (-4x + 4x) + (-4y + 4y) + y2 + 16

= x2 + 2xy + y2 + 42 = (x + y)2 + 42

b/ (x - y + 6)(x + y - 6) = x2 + xy - 6x - xy - y2 + 6y + 6x + 6y - 36 = x2 + (xy - xy) + (-6x + 6x) + (6y + 6y) - y2 - 36

= x2 - y2 + 12y - 62 = x2 - (y2 - 12y + 62) = x2 - (y2 - 2 . 6y + 62) = x2 - (y - 6)2

c/ (y + 2z - 3)(y - 2z - 3) = y2 -2yz - 3y + 2yz - 4z2 - 6z - 3y + 6z + 9 = y2 + (-2yz + 2yz) + (-3y - 3y) + (-6z + 6z) - 4z2 + 9

= y2 - 6y - 4z2 + 9 = (y2 - 6y + 9) - 4z2 = (y - 3)2 - (2z)2

d/ (x + 2y + 3z)(2y + 3z - x) = 2xy + 3xz - x2 + 4y2 + 6yz - 2xy + 6yz + 9z2 - 3xz = (2xy - 2xy) + (3xz - 3xz) - x2 + (6yz + 6yz) + 9z2 + 4y2

= -x2 + 4y2 + 12yz + 9z2 = (4y2 + 12yz + 9z2) - x2 = [ (2y)2 + 2 . 2 . 3yz + (3z)2 ] - x2 = (2y + 3z)2 - x2